Digital Marketing Training for UMKM of Tarakan City - Erick Karunia; Ahmad Juliana; Syahran; Ahmatang; Nurul Hidayat; Budi Hasyim; Muh. Irfandy Azis; Shalahuddin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
This Community Service activity was carried out by a team of management and accounting lecturers of the Faculty of Economics, University of Borneo Tarakan on Digital Marketing Training for UMKM in the city of Tarakan. This training aims to provide knowledge about digital marketing to UMKM in the city of Tarakan which was held on Juny 28 to 11 july, 2021. The method used is the current approach with the participatory method of rural approach in the form of training and mentoring which is generally done through three stages; preparation, training and evaluation, so that it can be more easily understood by UMKM in the city of Tarakan. Participants in this training are representatives of several people with a number of 30 people who have a profession as UMKM actors in the city of Tarakan, and who are still relatively young on average also fall into the category of beginners. The result obtained is to increase knowledge for MSMEs in the city of the importance of Digital Marketing (DM) to increase sales and for the sustainability of the business carried out. This activity is expected to help UMKM actors in increasing revenue and also improving the knowledge in the digital era so as not to be crushed by the changing times.